Bone mineral density in high-level endurance runners: part B—genotype-dependent characteristics - Herbert, A. J.; Williams, A. G.; Lockey, S. J.; Erskine, R. M.; Sale, C.; Hennis, P. J.; Day, S. H.; Stebbings, G. K. (European Journal of Applied Physiology, 2021)
Purpose Inter-individual variability in bone mineral density (BMD) exists within and between endurance runners and non-athletes, probably in part due to difering genetic profles. Certainty is lacking, however, regarding which genetic variants may contribute to BMD in endurance runners and if specifc genotypes are sensitive to environmental factors, such as mechanical loading via training.